Kafur and Champor in Islam, Malay, and Chinese History - Mohamad Herman Abdullah; Fadzli Adam; Indra Martian Permana; Fakhratu Naimah Muhad (TSAQAFAH, 2025)
Malay camphor (Dryobalanops aromatica) has played a significant role in the economy, Malay culture, and international trade since ancient times. It has been used in medicine, religious rituals, and diplomatic relations between major empires. Known as al-Kafur in the Quran and Hadith, it was also referred to as camphor by European traders. However, after the Industrial Revolution in the 19th century, Malay Camphor became increasingly marginalized when Chinese Camphor (Cinnamomum camphora, also known as Xiangzhang [樟树]) replaced it due to its lower cost. In 1903, the production of synthetic camphor, based on the chemical formula of Chinese Camphor (C10H16O), was patented as camphor, while the chemical formula of Malay Camphor (C10H18O) was designated as borneol, leading to confusion in scientific studies, Malay scholarship, and Islamic studies. This study examines the differences between Malay Camphor and Chinese Camphor and aims to determine which type is actually referenced in the Quran and Islamic history. A qualitative approach was employed, involving a literature review, analysis of Quranic and Hadith interpretations, and interviews with historians, botanists, and cultural practitioners in Barus. The findings indicate that Malay Camphor has a more fragrant aroma, a cooling effect, refreshing, free from harm, non-toxicity, and high quality. It is also edible and can be used as a flavoring agent—aligning with the characteristics of al-Kafurin Islamic interpretation. However, trade monopolies and terminological errors have obscured its identity in modern history. This study confirms that al-Kafurin Islam refers to Malay Camphor and highlights the importance of correcting terminological errors to ensure that camphor is associated with Dryobalanops aromatica rather than Xiangzhang.